Synthesis and Characterization of Polystyrene Sulfonic Acid from Expanded Polystyrene Foam as a Catalyst in the Synthesis of Triacetin - Renita Manurung; Rosdanelli Hasibuan; Fatimah Batubara; Handy Inarto; Alwi Gery Agustan Siregar; Auryn Saputra (Indonesian Journal of Chemistry, 2021)
In Indonesia, the composition of waste has gradually changed over time. To reduce expanded polystyrene (EPS) foam waste, we converted it into a heterogeneous acid catalyst, namely Polystyrene Sulfonic Acid (PSSA). The catalyst was then used in an esterification reaction to generate triacetin. In this research, the synthesis of PSSA was performed using a sulfonation reaction with silver sulfate (Ag2SO4) as the catalyst. Based on FTIR analysis, the sulfonation reaction was successful. The use of 0.5% and 1% catalysts led to a significant increase in the degree of sulfonation of PSSA, while there was a relatively constant increase when using 1.5–2.5% catalysts. The highest degree of sulfonation (78.63%) was achieved when the reaction was performed using 2% Ag2SO4 catalyst for 25 min. The PSSA with the highest degree of sulfonation was characterized using X-Ray Diffraction (XRD), SEM-EDX, and BET-BJH. This PSSA had a semi-crystalline structure with a crystallinity of 73.83%, a particle size of 1.75 nm, mesoporous pores with a radius of 16.984 Å, and a sulfur content of 15% (% mass).